Fate of patients with prehospital resuscitation for ST-Elevation myocardial infarction and a high rate of early reperfusion therapy: (results from the PREMIR [prehospital myocardial infarction registry]) - Koeth, Oliver; Schneider, Steffen; Zahn, Ralf; Zeymer, Uwe (The American journal of cardiology, 2012)
Patients with acute ST-segment elevation myocardial infarction (STEMI) needing prehospital cardiopulmonary resuscitation (CPR) have a very high adverse-event rate. However, little is known about the fate of these patients and predictors of mortality in the era of early reperfusion therapy. From March 2003 through December 2004, 2,317 patients with prehospital diagnosed STEMI were enrolled in the Prehospital Myocardial Infarction Registry. One hundred ninety patients (8.2%) underwent prehospital CPR and were included in our analysis. Overall 90% of patients were treated with early reperfusion therapy, 56.3% received prehospital thrombolysis and 1/2 of these patients received early percutaneous coronary intervention after thrombolysis, 28.4% of patients were treated with primary percutaneous coronary intervention, and 5.3% received in-hospital thrombolysis. Total mortality was 40.0%. The highest mortality was seen in patients with asystole (63%) or pulseless electric activity (64%). Independent predictors of mortality were need for endotracheal intubation and older age, whereas ventricular fibrillation as initial heart rhythm was associated with survival. In conclusion, in this large registry with prehospital diagnosed STEMI, incidence of prehospital CPR was about 8%. Even with a very high rate of early reperfusion therapy, in-hospital mortality was high. Especially in elderly patients with asystole as initial heart rhythm and with need for endotracheal intubation, prognosis is poor despite aggressive reperfusion therapy.